InvestiGATORS - Green, John Patrick, 1975- (Green, John Patrick, 1975- InvestiGators (Series), 2020)
With their Very Exciting Spy Technology and their tried-and-true, toilet-based travel techniques, the InvestiGators are undercover and on the case! And on their first mission together, they have not one but two mysteries to solve! Can Mango and Brash uncover the clues, crack their cases, and corral the crooks<U+2015>or will the criminals wriggle out of their grasp?